A scoping review of qualitative studies about children experiencing parental separation. (May 2013) - Birnbaum, Rachel; Saini, Michael
This article explores a scoping review of qualitative studies about children's experiences and feelings during times of parental separation. The purpose of the review was to explore children's feelings and attitudes about their parents' separation and how their voices are heard during times of parental separation. The scoping review examined 44 studies in 13 countries involving 1525 children. While the studies examine how and why children's voices are important in the decision-making process adults typically remain the gatekeepers of their voices. Children's participation in child custody decision-making must include them at all levels of practice, policy and research.